Kelayakan Media Pembelajaran iSpring Suite Berbasis Android pada Mata Pelajaran Shorof - Vera Fikrotin; Siti Sulaikho (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
Shorof learning is not easy for VIII grade students. Therefore, shorof is a branch of grammar Arabic, not a language mother. Caused, iSpring Suite learning media hope to increase attracted learners to study shorof. This research aims to determine the feasibility iSpring Suite learning media based on android of short subject for VIII grade students. This study uses the research and development method using Thiagarajan 4 D theory; they are defined, designed, developed, and disseminated. The instrument of study used material expert, media expert, language expert, and questionnaire of students. The result of the data is 81.25% includes the Very Good category of an expert. 70.45% includes the Good category of media experts. 96.87% includes the Very Good category of a language expert, and 87.19% includes questionnaire response students. So, based on the result, it determines of iSpring Suite learning media is “Very Good” to use.